Answers

2014-04-02T19:47:50+05:30
(a^m)*(a^n) = a^m+n
(a^m)/(a^n)=a^m-n
0
2014-04-02T20:10:12+05:30
Rule 1:- Any no. exept zero, whose index is 0 is always = to 1.
             a0=1
rule 2:- a-m = 1/m0
rule 3:- to multiply expressions with the same base copy the base and add the indices.
           a to the power m * a to the power n = a to the power m+n
rule 4:- to divide expressions with the same base, copy the base and seek the indices.
               a to the power m divided by a to the power n = a to the power m-n.
rule 5:- to raise an expression nth index copy the base and multiply the indices.
rule 6 :- a to the power m / n = n√a to the power m = ( n√a to the power m.
1 5 1